Development of musical culture of preschool children based on folk traditions - Abduvalieva Khayrinso Abdurasul kizi (Genius Journals, 2023)
A child's relationship with singing folk songs, playing folk instruments, and listening to folk music should start at a very young age. Our research study, which involved teachers and parents of preschoolers, aimed to find out how much time families and kindergarten classes spend singing or listening to folk songs and playing folk instruments, as well as what level of interest preschoolers, their parents, and their teachers have in folk music.
Keywords: folk songs; singing; playing; preschoolers